Gasdermin A (GSDMA) Tissue Expression, Serum and Urinary Concentrations With Clinicopathologic Outcome in Psoriasis - Julia Nowowiejska; Anna Baran; Anna Pryczynicz; Justyna Hermanowicz; Beata Sieklucka; Dariusz Pawlak; Iwona Flisiak (Mattioli1885, 2024)
Introduction: Psoriasis is a frequent and incurable skin disease that is an important issue in contemporary dermatology, whereas its pathogenesis is still uncertain. Gasdermin A (GSDMA) is a member of the gasdermin protein family that enables pore formation in cellular membranes leading to cell death called pyroptosis. Objective: Our aim was to investigate the role of GSDMA in psoriatic patients. Method: The study enrolled 60 patients with active plaque-type psoriasis and 30 sex- and age-matched volunteers without dermatoses. GSDMA concentration was assessed in serum and urine samples of all participants using ELISA. GSDMA tissue expression was assessed by immunohistochemistry. Results: GSDMA serum concentration was significantly higher in patients compared to controls, whereas urinary GSDMA/creatinine ratio was insignificantly lower. GSDMA tissue expression was more prominent in psoriatic plaque compared to non-lesional patient skin and healthy skin of subjects without dermatoses. There was a strong negative correlation between GSDMA serum concentration and alanine aminotransferase (ALT) activity. GSDMA did not correlate with PASI or psoriasis duration. Conclusions: Obtained results point to the probable involvement of GSDMA in psoriasis. GSDMA overexpression may probably lead to keratinocytes hyperproliferation and be responsible for triggering inflammation in psoriatic skin. Serum GSDMA, but not urinary GSDMA, could become psoriasis biomarker.